KONSEKUENSI YANG TIMBUL DARI ASAS LEGALITAS DALAM HUKUM PIDANA MATERIIL - Pristiwati, Endang (Universitas Islam Negeri Antasari Banjarmasin, 2013)
The principle of legitimacy as a state aims to protect the society, which is expressed in the principle of legality. While the purpose of the law is more fundamental justice. This principle is officially defined as what is just stated by the constitution. This definition however has been left by some developed countries which is according to them could not be extended in its application. Therefore the definition of the principle of legitimacy should be expanded comprehensively in order reach wider consequence in the law and constitution. Substantive legality principle holds that the main purpose of the law is that justice can be realized based on the laws that have a broader scope than just the law, so it should have been in Indonesia also have to switch the view of the use of formal legality principle to the principle of legality material.